Botrytis cinerea bunch rot of table grapes : colonization and timing of fungicide application - De Kock, Petrus Jurie (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1989.